A Framework for Regulating Microfinance Institutions : The Experience in Ghana and the Philippines - Gallardo, Joselito (World Bank, Washington, DC, 2013)
An earlier Policy Research Working Paper (Hennie van Greuning, Joselito Gallardo, and Bikki Randhawa, "A Framework for Regulating Microfinance Institutions," WPS 2061, February 1999) presented a regulatory framework that identifies thresholds in financial intermediation activities that trigger a requirement for a microfinance institution to satisfy external or mandatory guidelines-a tiered approach to regulation and prudential supervision. The model focuses on risk-taking activities of microfinance institutions that must be managed and prudentially regulated. The author reports on the results of the field testing and assessment of the tiered approach, focusing on the experience of Ghana and the Philippines. The two countries both have a wide range of informal, semi-formal, and formal institutions providing financial services to the poor, but differ in how they regulate financial intermediation activities by microfinance providers. In his assessment and a comparative analysis, the author focuses on key issues in the regulatory and supervisory environment for microfinance-and in the legal system and judicial processes-being addressed by government authorities and microfinance stakeholders in both countries. He gives particular attention to the thresholds at which intermediation activities become subject to prudential regulation and regulatory standards for capitalization and capital adequacy, asset quality and provisioning for nonperforming loans, and liquidity management. seeks to identify the key elements and characteristics of the microfinance regulatory experience of Ghana and the Philippines and to draw the lessons that may be useful for other countries interested in establishing a regulatory environment conducive to the development of sustainable microfinance institutions. The experience of Ghana and the Philippines shows that a transparent, inclusive regulatory framework is indispensable for enabling microfinance institutions to maintain market specialization and to pursue institutional development that leads to sustainability. Clear pathways for institutional transformation facilitate the integration of microfinance institutions into the formal financial system.